Bioterrorism versus radiological terrorism: Notes from a bio/nuclear epidemiologist - Goffman, MD, FACP, Thomas E. (American Journal of Disaster Medicine, 2009)
The antiterrorism and disaster planning communities often speak of the high potential for bioterrorism and possible potential for radioterrorism, specifically the explosion of a fission device on US soil. Information gained from an epidemiologist’s work in the national and international scene, which inevitably involves Intel regarding the cultures and subcultures being studied, suggest that bioterrorism is far less likely to be a major threat, that has been over-emphasized at the state level due to warnings from Homeland Security, and that Homeland Security itself appears biased toward bioterrorism of late with very little available rational basis.